Warming and top predator loss drive direct and indirect effects on multiple trophic groups within and across ecosystems. Issue 2 (1st December 2021) - Antiqueira, Pablo Augusto P.; Petchey, Owen L.; Rezende, Felipe; Machado Velho, Luiz Felipe; Rodrigues, Luzia Cleide; Romero, Gustavo Quevedo
Abstract: The interspecific interactions within and between adjacent ecosystems strongly depend on the changes in their abiotic and biotic components. However, little is known about how climate change and biodiversity loss in a specific ecosystem can impact the multiple trophic interactions of different biological groups within and across ecosystems. We used natural microecosystems (tank‐bromeliads) as a model system to investigate the main and interactive effects of aquatic warming and aquatic top predator loss (i.e. trophic downgrading) on trophic relationships in three integrated food web compartments: (a) aquatic micro‐organisms, (b) aquatic macro‐organisms and (c) terrestrial predators (i.e. via cross‐ecosystem effects). The aquatic top predator loss substantially impacted the three food web compartments. In the aquatic macrofauna compartment, trophic downgrading increased the filter feeder richness and abundance directly and indirectly via an increase in detritivore richness, likely through a facilitative interaction. For the microbiota compartment, aquatic top predator loss had a negative effect on algae richness, probably via decreasing the input of nutrients from predator biological activities. Furthermore, the more active terrestrial predators responded more to aquatic top predator loss, via an increase in some components of aquatic macrofauna, than more stationary terrestrial predators. The aquatic trophic downgrading indirectly altered the richness and abundance of cursorial terrestrial predators, but these effects had different direction according to the aquatic functional group, filter feeder or other detritivores. The web‐building predators were indirectly affected by aquatic trophic downgrading due to increased filter feeder richness. Aquatic warming did not affect the aquatic micro‐ or macro‐organisms but did positively affect the abundance of web‐building terrestrial predators. These results allow us to raise a predictive framework of how different anthropogenic changes predicted for the next decades, such as aquatic warming and top predator loss, could differentially affect multiple biological groups through interactions within and across ecosystems. Abstract : This study allowed the authors to raise a predictive framework of how different anthropogenic changes predicted for the next decades, such as aquatic warming and top predator loss, could differentially affect multiple biological groups through interactions within and across ecosystems. Resumo: As interações interespecíficas dentro e entre ecossistemas adjacentes dependem fortemente das mudanças de seus componentes abióticos e bióticos. Entretanto, pouco se sabe sobre como mudanças climáticas e a perda de biodiversidade em um ecossistema específico pode impactar as múltiplas interações tróficas de diferentes grupos biológicos dentro e entre ecossistemas. Nós utilizamos micro ecossistemas naturais (bromélias‐tanque) como sistema modelo para investigar os efeitos individuais e interativos do aquecimento e da perda de predadores aquáticos (simplificação trófica) nas relações tróficas em três compartimentos integrados da teia alimentar: i) micro‐organismos aquáticos, ii) macroorganismos aquáticos e iii) predadores terrestres (via efeito entre ecossistemas). A perda de predadores de topo aquáticos afetou substancialmente os três compartimentos da rede trófica. No compartimento da macrofauna aquática, a simplificação trófica aumentou a riqueza e abundância de filtradores, direta e indiretamente, por meio de um aumento da riqueza de espécies de detritívoros, provavelmente através de uma interação de facilitação. Para o compartimento da microbiota, a perda de predadores de topo aquáticos teve um efeito negativo sobre a riqueza de espécies de algas, provavelmente por meio da diminuição da entrada de nutrientes provenientes das atividades biológicas dos predadores. Além disso, os predadores terrestres mais ativos responderam mais à perda de predadores de topo aquáticos, por meio de um aumento de alguns componentes da macrofauna aquática, do que predadores terrestres mais estacionários. A simplificação trófica aquática alterou indiretamente a riqueza e abundância de predadores cursoriais terrestres, mas esses efeitos tiveram direção diferente de acordo com o grupo funcional aquático, filtradores ou outros detritívoros. Os predadores construtores de teias foram indiretamente afetados pela simplificação trófica aquática devido ao aumento da riqueza de filtradores. O aquecimento aquático não afetou os micro ou macro organismos aquáticos, mas afetou positivamente a abundância de predadores terrestres construtores de teias. Esses resultados nos permitem levantar um quadro preditivo de como diferentes mudanças antropogênicas preditas para as próximas décadas, como o aquecimento e a perda de predadores de topo aquáticos, podem afetar diferencialmente vários grupos biológicos por meio de interações dentro e entre os ecossistemas.